Family and Career. Future plans for university students. Ed. Ágnes Engler. - Csaba Jancsák (Debrecen University Press, 2020)
Bibliography of the reviewed book: Engler, Á. (2018). Future plans for university students. Debrecen: Center for Higher Education Research and Development. p. 212., ISBN 978-615-80077-6-4.